2001
DOI: 10.1007/s004280100437
|View full text |Cite
|
Sign up to set email alerts
|

Predominant expression of fibroblast growth factor (FGF) 8, FGF4, and FGF receptor 1 in nonseminomatous and highly proliferative components of testicular germ cell tumors

Abstract: Nonseminomatous components within testicular germ cell tumors affect patient prognosis to varying degrees. These components are well known to mimic early embryonic totipotential tissues. Prompted by the recent observation that fibroblast growth factor (FGF) 8, FGF4, and FGF receptor (FGFR) 1 are required for the growth of early postimplantational embryonic tissues, we investigated the expressions of FGF8, FGF4, and FGFRI in surgically resected specimens of primary testicular germ cell tumors using an immunohis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 14 publications
(16 reference statements)
0
17
0
1
Order By: Relevance
“…Pluripotent potential germ-cell neoplasms, like IGCNU, seminoma, and embryonal carcinoma, are labeled with antibodies against PLAP, c-KIT [12], OCT3/4 (POU5F1) [15], and CD30 [18]. On the other hand, for differentiated GCT, several growth factors, growth factor receptors, and transcription factors have been reported in neoplastic cells but with various frequencies and variable specificity [8,11,21]. This study confirmed the outstanding specificity of GPC3 to differentiated GCT, such as in "the double layer pattern", glandular structures of embryonal carcinoma encircled by a row of flattened YST cells [1,3], in MGCT in which OCT3/4 and GPC3 immunoreactivities were mutually exclusive.…”
Section: Discussionmentioning
confidence: 99%
“…Pluripotent potential germ-cell neoplasms, like IGCNU, seminoma, and embryonal carcinoma, are labeled with antibodies against PLAP, c-KIT [12], OCT3/4 (POU5F1) [15], and CD30 [18]. On the other hand, for differentiated GCT, several growth factors, growth factor receptors, and transcription factors have been reported in neoplastic cells but with various frequencies and variable specificity [8,11,21]. This study confirmed the outstanding specificity of GPC3 to differentiated GCT, such as in "the double layer pattern", glandular structures of embryonal carcinoma encircled by a row of flattened YST cells [1,3], in MGCT in which OCT3/4 and GPC3 immunoreactivities were mutually exclusive.…”
Section: Discussionmentioning
confidence: 99%
“…Low level of Fgf8 mRNA is also expressed by the epididymis [3]. Interestingly, high levels of FGF8 are expressed in prostatic [20][21][22] and testicular [23] cancers. Previous studies have shown that FGF8 can promote tumorigenic properties, such as growth, invasiveness, and the angiogenic, migratory, and metastatic capacity of breast and prostate cancer cells [24][25][26][27], and can induce tumorigenesis in the mouse prostate [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Segundo a literatura, a atividade proliferativa celular pode ser influenciada por outros FGFs: FGF4 (Baczyk et al, 2005;Suzuki et al, 2001), FGF7 (Palmieri et al, 2003), FGF8 (Suzuki et al, 2001;Xu et al, 1998), FGF9 (Miyagi et al, 1999) e FGF10 (Xu et al, 1998 Mol. Cell.…”
Section: Resultsunclassified